The study of the anti-inflammatory properties of carotenoid liquid extracts on the model of adjuvant-induced inflammation - Boiko, Yurii; Ayat, Mohammed; Boiko, Irina; Shandra, Alexey (ScienceRise: Biological Science, 2021)
The search for new anti-inflammatory substances is an important area of pharmacology. Plant carotenoids have many positive biological effects and are of interest as potential anti-inflammatory agents. The aim. To study the anti-inflammatory properties of extractive carotenoids from fruits of Capsicum annuum L. on the model of adjuvant-induced inflammation. Materials and methods. The fruits of Capsicum annuum L. were used as the plant raw material. Carotenoids were obtained by the extractive method. The model of adjuvant-induced inflammation was reproduced in young female rats. The dynamics of changes in the volume of the inflammatory edema and the total number of blood leukocytes were studied. Results and discussion. A decrease in edema in nonspecific inflammation was observed on day 15 during the therapy with carotenoid extracts (Δ1.01±0.08 in treatment group; Δ1.28±0.08 in control group). For specific inflammation, edema reduction when using carotenoids occurred on day 30 (Δ0.047±0.015 in treatment group; Δ0.073±0.012 in control group). A decrease in leukocytosis occurred on days 20 and 30 of the treatment for non-specific and specific inflammation, respectively. The mechanisms of the anti-inflammatory action of carotenoids are presumably associated with the antioxidant effect and the ability to affect the production of pro-inflammatory cytokines. Conclusions. Extractive carotenoids from the fruits of Capsicum annuum L. have the anti-inflammatory activity in the case of adjuvant-induced inflammation. Treatment with Capsicum annuum L. extract reduced inflammatory edema and total leukocyte count